Independent real time localization system for iphone : research and its healthcare application - Lv, Xintong. (2014)
This project studied several popular localization algorithms on the iPhone and, according to the demands, specifically designed the software to improve healthcare IT system in hospitals. The challenge of this project was to realize the different localization systems on the iPhone and to make balance between its response time and localization accuracy. We implemented three popular localization algorithms, namely nearest neighbor (NN), K-nearest neighbor (KNN), and probability phase, and compared their performance on the iPhone. Furthermore, we also implemented a real-time localization system using the ZigBee technology on the iPhone. Thus, the whole system could realize not only self-localization but also others-localization. To fulfill the healthcare needs, we developed an application, which can be used to improve the hospital IT system. The whole project included three phases. The first phase was to localize the iPhone's position using the received Wi-Fi signal by the iPhone, compare and optimize their performances. During the second phase, we implemented a ZigBee RFID localization system and combined it with the Wi-Fi system. Finally, we combined new features of the system with a healthcare IT system. We believe that this application on the iPhone can be a useful and advanced application in hospitals.